The Effectiveness of Education Using Monopoly Media on Increasing the Knowledge and Attitudes of Teenage Girls About Anemia Prevention - Sylvia Huriyanti Taufik; Utami Putri Kinayungan; Nur Fauzia Asmi; Deni Alamsah (International Journal of Health Engineering and Technology, 2025)
Anemia remains a significant public health issue among adolescent girls in Indonesia, impacting physical development, cognitive function, and productivity. This study aimed to analyze the effectiveness of nutrition education using monopoly game media in increasing knowledge and attitudes regarding anemia prevention among adolescent girls. A quasi-experimental pretest-posttest control group design was employed, involving 92 female students from SMAN 3 Cikarang Utara, selected through purposive sampling. The intervention group received nutrition education via monopoly games, while the control group received conventional lectures. Data were collected using validated questionnaires and analyzed with univariate and bivariate methods, including the Wilcoxon test, using SPSS. The results showed significant improvements in both knowledge and attitudes in both groups, with the monopoly game group demonstrating a higher increase. The findings indicate that interactive educational media, such as monopoly games, are effective in enhancing knowledge and attitudes toward anemia prevention. It is recommended that schools integrate such interactive methods into health education programs.